A brief history of menstruation - Karaboue, Karidia (Medicina Historica, 2024)
The most demonised of all biological events is linked to blood and is that of menstruation. Menstruation can be perceived as an alienating experience, a loss of control over one's body, and an act of internal self-sabotage with harmful consequences. However, it is also a phenomenon influenced by cultural, economic, medical and political factors. Caught between science and politics, beliefs and medicine, and despite its affecting millions of women worldwide every month, it remains taboo.